How to apply Premium Remedium in the Taxation Sector - Christwan Christwan; Khalimi Khalimi; Arief Wibisono (Publikasi Indonesia, 2024)
Criminal law enforcement against tax crimes in Indonesia has raised debates regarding applying the premium remedium or ultimum remedium principle. This study explores the legal issues arising from this change, including the submission of a judicial review of Article 39 paragraph (1) letters d and i by a taxpayer, which is considered to have a premium remedium nuance. This article examines the application of criminal law to tax crimes in Indonesia in the context of the self-assessment system and the amended regulations. With a normative approach, this study aims to assess whether criminal law in tax crimes tends to be more on the ultimum remedium or premium remedium principle, and to highlight the harmonization between the self-assessment system and criminal law enforcement. This study finds that the application of criminal law to tax crimes in Indonesia tends to follow the ultimum remedium principle, where criminal sanctions are used as a last resort after administrative measures are ineffective. Despite the elimination of Article 13A in the KUP Law which has raised debates regarding the application of premium remedium, law enforcement still emphasizes taxpayer compliance in the self-assessment system. In addition, the KUP Law also accommodates the termination of investigations in the interests of state revenue if taxpayers are willing to pay their tax obligations.